Studies on Growth Correlations in Pinus rlliottii - Gurumurti, K.; Srivastava, V. K. (Indian Forester, 1984)
Investigations on growth analysis in Pinus elliottii, which has high rate of productions revealed that there is a close correlation between total biomass, leaf area as well as leaf efficiency. The results suggest that during early stages canopy growth is vertical and subsequently horizontal. The leaf efficiency though increases with age, the rate of increase declines with age. Net assimilation rate shows a fluctuating trend and the mean NAR is much higher when compared to other conifers which explains the higher turnover of dry matter in this species.